Disposition kinetics of ampicillin in Bubalus bubalis calves - ALAM, M; BANERJEE, N C; YADAVA, K P (The Indian Journal of Animal Sciences, 2013)
The pharmacokinetics of ampicillin after single i/v dose (10 mg/kg bw) was studied in a group of buffalo calves. The piasma drug concentration declined from 19.83±0.35 ug/ml to 0.22±0.01 up to 12hr. The mean values of kinetic parameters for t1/2a, t1/2B. vdarea: CI8 and T/P ratio were 0.24±0.02 hr. 2.90±0.11 hr, 1.56±0.08 L/kg. 6.22±0.21 ml/kg/min, and 4.87±0.27 respectively. The mean values of K12 , K21 K2 and K,/K21 were 1.17±0.13 hr-1 . 0.47±0.02 hr-1. 1.40±0.06 hr-1 and 2.42±0.18 respectively. The per cent protein binding (in vitro) of ampicillin in the plasma of butfalo calves ranged from 19.25 to 28.09. Dosage regimen based on the kinetics of drug has been suggested for optimal clinical eflicacy.